Incidencia de las mermas en los costos de producción de la fábrica de productos lácteos abellito s.a., barrio la Avelina, parroquia Tanicuchi, cantón Latacunga, provincia Cotopaxi - Calapaqui Toaquiza, Jhohana Maribel (2017)
This research project was developed with the purpose of determine the waste causes that origin during the production process, and how they fall on the cost of “ABELLITO S.A.” daily products factory, located in La Avelina neighborhood, Tanicuchi parish Latacunga city, that has been affected by the decrease of raw material and supplies, provoking huge losses and cost raising which don’t reflect in the sale price due to market competition. For the data and information compilation in the relation with the problem, it was used a qualitative approach, taking into consideration the field research that carried out to know the current enterprise situation, based on documental research it was sustained the scientific and theoretical information, initially exploratory method was used to establish the obstacles of the daily products factories specially at “ABELLITO S.A.”, industry, finally descriptive method and the observation were applied , that permitted to define the problem using graphic and analytic techniques, revealing that the 50% of the company is affected due to the wastes and the production costs rising, information that shows a certain balance or ignorance in the company staff, thus it was determined that the waste incidence in the production cost begin with the raw material cost and in the indirect manufacturing costs, provoking a decline in the productive level of the industry that is reflected in the company utilities at the end of each economic period. The principal productions steps which the raw material tends to decrease in greater quantity are; the reception and, lab, transportation from warehouse to production and even during the packing process, for that reason through the research result the company will be able to apply new registry methods and waste control achieving to improve the production and increase its sales and clients to promote the sector growth.